2011
DOI: 10.1016/j.gynor.2011.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Unusual liver locations of growing teratoma syndrome in ovarian malignant germ cell tumors

Abstract: ► Growing teratoma syndrome (GTS) with unusual liver locations are described after fertility preserving surgery and chemotherapy treatment for mixed malignant ovarian germ cell tumors (MGCT). ► It's a rare syndrome of mixed malignant ovarian germ cell tumors and in both cases enlarged and growing liver masses appeared during cisplatin-etoposide-bleomicin (BEP) chemotherapy. ► Radiological exams (CT scan and MRI) were suggestive for secondary metastasis and serum markers became negative during chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…[18][19][20][21][22] In contrast, GTS after ovarian immature teratoma can either have a retroperitoneal nodal spread or present with diffuse peritoneal disease, similar to other ovarian malignancies. [23][24][25][26][27][28][29] The proposed surgery usually is a so-called ''debulking'' surgery, a term conventionally used for the removal of the intraabdominal tumor in ovarian cancer, However, the literature has little data regarding the extent of surgery required, particularly the place of fertilitysparing surgery or the clinical outcome after debulking for intraabdominal GTS. Because GTS is significantly less frequent in women than in men, published series are short, and none have focused specifically on the question of surgical management and postsurgical outcomes.…”
mentioning
confidence: 99%
“…[18][19][20][21][22] In contrast, GTS after ovarian immature teratoma can either have a retroperitoneal nodal spread or present with diffuse peritoneal disease, similar to other ovarian malignancies. [23][24][25][26][27][28][29] The proposed surgery usually is a so-called ''debulking'' surgery, a term conventionally used for the removal of the intraabdominal tumor in ovarian cancer, However, the literature has little data regarding the extent of surgery required, particularly the place of fertilitysparing surgery or the clinical outcome after debulking for intraabdominal GTS. Because GTS is significantly less frequent in women than in men, published series are short, and none have focused specifically on the question of surgical management and postsurgical outcomes.…”
mentioning
confidence: 99%
“…The previous study reported that the presence of mature teratoma in the first tumor, the incomplete resection, and the absence of volume mass reduction during chemotherapy were predictors. [ 4 ] Recent studies revealed that the patient who developed GTS tended to have more advanced stage and were more likely to have received chemotherapy. [ 1 3 ] The median interval from diagnosis of GCT to development GTS was 7–26.6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mass was closely related to the inferior surface of right lobe of liver, there was no parenchymal involvement. In literature review, GTS has been presented in two patients as intraparenchymal liver masses both underwent surgical excision and had uneventful follow-up 12. A more aggressive hepatic involvement of GTS was reported in one case where extensive teratoma growth replaced the entire liver and the patient underwent a successful liver transplantation 13…”
Section: Discussionmentioning
confidence: 99%